2016
DOI: 10.4238/gmr.15027723
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice variant of the bovine GALNTL5 gene identified in Chinese Holstein bull testis tissue and its mRNA expression

Abstract: ABSTRACT. The polypeptide N-acetylgalactosaminyltransferase-like protein 5 (GALNTL5) is a newly identified protein that is specifically expressed in testis tissue and participates in spermatogenesis. In this study, we characterized a novel bovine GALNTL5 splice variant, designated as GALNTL5-AS, by using real-time polymerase chain reaction (RT-PCR) and clone sequencing methods. The novel GALNTL5 isoform was derived from the complete transcript, GALNTL5-complete, via alternative splicing (AS). The pattern of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Currently, GALNTL was found in male reproductive organs in rodents and cattle [40][41][42][43]. A KEGG pathway analysis indicated that GALNT6 participates in mucin-type-O-glycan biosynthesis in the canine ES [31].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, GALNTL was found in male reproductive organs in rodents and cattle [40][41][42][43]. A KEGG pathway analysis indicated that GALNT6 participates in mucin-type-O-glycan biosynthesis in the canine ES [31].…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylgalactosaminyltransferase-like proteins (GALNTL) were found in male reproductive organs in rodents and cattle [ 110 , 111 , 112 , 113 ]. In canines, it has been shown that polypeptide N-acetylgalactosaminyltransferase 6 (GALNT6) is important for epididymal sperm motility [ 27 ] and participates in mucin-type-O-glycan biosynthesis [ 26 ].…”
Section: Protein Markersmentioning
confidence: 99%